Colleters in Cephalanthus (Rubiaceae) and reevaluation of occurrence of corolline colleters in Angiosperms - Romero, María Florencia (2022)
Colleters are glandular structures related to young shoots protection. In several Angiosperm families, as in Rubiaceae colleters are taxonomically important. This study reports presence, location, morpho-anatomical structure, ontogeny and histochemistry of colleters in vegetative and reproductive organs in 6 species of Cephalanthus and 20 species representatives of the tribe Naucleeae. Primarily based on their color and their secretion color, they were classified into light (LC) and dark (DC) colleters. The LC are exclusive to the inner side of the stipule, while the DC are found in several vegetative and reproductive organs. Histochemical studies revealed that higher mucilage and phenol content in DC could explain the dark color secretion. Results were analyzed at genus, tribe and subtribe levels, evidencing the taxonomic relevance in the family. Finally, the presence of corolline colleters in angiosperm flowers was reviewed. It was confirmed that, besides Cephalanthus, they are only present in Adenoa (Passifloraceae) and Chamaecrista (Fabaceae). Therefore, structures described as colleters in Nerium (Apocynaceae) and Cuscuta (Cuscutaceae) corollas do not correspond to colleters. This proves that corolline colleter is a rare character in Angiosperms. To conclude we provide a record of presence/absence, type and distribution of corolline colleters in an Angiosperm phylogenetic tree.